Genomic analysis of carbapenemase-producing Enterobacteriaceae in Queensland reveals widespread transmission of blaIMP-4 on an IncHI2 plasmid. Issue 1 (20th December 2019) - Roberts, Leah W.; Catchpoole, Elizabeth; Jennison, Amy V.; Bergh, Haakon; Hume, Anna; Heney, Claire; George, Narelle; Paterson, David L.; Schembri, Mark A.; Beatson, Scott A.; Harris, Patrick N. A.
Abstract : Carbapenemase-producing Enterobacteriaceae (CPE) are an increasingly common cause of healthcare-associated infections and may occasionally be identified in patients without extensive healthcare exposure. bla IMP-4 is the most frequently detected carbapenemase gene in Enterobacteriaceae within Australia, but little is known about the mechanisms behind its persistence. Here we used whole genome sequencing (WGS) to investigate the molecular epidemiology of bla IMP-4 in Queensland, Australia. In total, 107 CPE were collected between 2014 and 2017 and sent for WGS on an Illumina NextSeq500. Resistance genes and plasmid types were detected using a combination of read mapping and nucleotide comparison of de novo assemblies. Six isolates were additionally sequenced using Oxford Nanopore MinION to generate long-reads and fully characterize the context of the bla IMP-4 gene. Of 107 CPE, 93 carried the bla IMP-4 gene; 74/107 also carried an IncHI2 plasmid, suggesting carriage of the bla IMP-4 gene on an IncHI2 plasmid. Comparison of these isolates to a previously characterized IncHI2 plasmid pMS7884A (isolated from an Enterobacter hormaechei strain in Brisbane) suggested that all isolates carried a similar plasmid. Five of six representative isolates sequenced using Nanopore long-read technology carried IncHI2 plasmids harbouring the bla IMP-4 gene. While the vast majority of isolates represented ﻿ E. hormaechei, several other species were also found to carry the IncHI2 plasmid, including Klebsiella species, Escherichia coli and Citrobacter species. Several clonal groups of E. hormaechei were also identified, suggesting that persistence of bla IMP-4 is driven by both presence on a common plasmid and clonal spread of certain E. hormaechei lineages.